Testing Theories of Redistribution: Structure of Inequality, Electoral Institutions, and Partisan Politics - Evelyne Huber; Itay Machtei; John D. Stephens (Luxembourg Income Study (LIS), 2023)
We re-analyze the major explanations of redistribution including the Meltzer-Richard (MR) model, power resources theory (PRT), the Iversen-Soskice political institutions explanation, Lupu and Ponstusson's wage inequality skew, along with works suggesting other causes, such as immigration. The paper reconsiders the causal chain posited in the various theories. We find that partisan government is directly related to redistribution and has a strong effect on the generosity of social policy. Lupu and Pontusson's wage dispersion skew measure has no effect on redistribution but does have a positive effect on generosity of social policy. In contrast, the MR measure is consistently highly significant but negative. Our analysis is based on a comprehensive data set on inequality in the working age population drawing on three sources; our own analyses of LIS and Eurostat SILC microdata and OECD macro data. The combined data set consists of 504 country year for the period 1969 to 2019.
Keywords: 330